The effect of Foreign Direct Investment (FDI) inflow towards Gross Domestic Product (GDP) in developed and developing countries / Marianne Jaraw @ Paul - Jaraw @ Paul, Marianne (2018)
This study is conducted in order to determine the impact of Foreign Direct Investment towards Gross Domestic Product in developed and developing countries. Statistical and Data analysis Software (STATA) version 12 was used to assess the prospective relationships between the Gross Domestic Product and the Foreign Direct Investment include other variables that affect the Gross Domestic Product which are Inflation, Export, Import, and Interest rate. Samples of 25 developed countries and 25 developing countries are selected ranging for 8 years from 2009 to 2016. Based on the finding, developed countries model is pooled by fixed effect and the regression test revealed that FDI has a positive relationship and significance with GDP. On the other hand, the developing countries model is pooled random effect and regression test revealed that the FDI have a positive relationship but not significant with GDP. It can be concluded that FDI contribute to the GDP.